Human Milk Oligosaccharides and Infant Weight in the First 6 Months of Life (P11-053-19). (13th June 2019) - Berger, Paige; Plows, Jasmine; Jones, Roshonda; Alderete, Tanya; Yonemitsu, Chloe; Ryoo, Ji Hoon; Bode, Lars; Goran, Michael
Abstract: Objectives: The effects of breastfeeding on reduced risk of obesity are inconclusive, although smaller studies suggest that specific human milk components may be relevant to infant weight gain. The primary aim of this study was to determine whether individual human milk oligosaccharides (HMOs) in the first month of life are associated with infant weight in the first 6 months of life. A secondary aim was to assess associations separately by HMO secretor status. Methods: Participants were 156 Hispanic mother-infant pairs. Breast milk was collected at 1 month. HMO composition was analyzed using high-pressure liquid chromatography, and HMO secretor status was determined by the presence or near absence of 2'-fucosyllactose or lacto-N-fucopentaose (LNFP) I. Infant weight was measured at 1 and 6 months, and infant weight-for-age z scores (WAZ) and WAZ changes were calculated. Multiple linear regressions were used to examine the effect of HMO composition on WAZ, adjusting for maternal age, pre-pregnancy BMI, infant age, sex, and birth weight. Results: In the total sample, HMO composition at 1 month was not significantly associated with WAZ at 1 month. In the total sample, higher LNFPII at 1 month predicted lower WAZ gain (β = –0.27, P = 0.01) and lower WAZ status (β = –0.26, P = 0.01) at 6 months. In infants of secretor mothers, higher LNFPII at 1 month predicted lower WAZ gain at 6 months (β = –0.23, P = 0.02); in infants of non-secretor mothers, LNFPII at 1 month predicted lower WAZ status at 6 months (β = –0.40, P = 0.03). Similar significant associations were observed when infant weight replaced WAZ in the models. No other HMOs were significantly related to infant WAZ or weight. Conclusions: Our data suggest that greater exposure to LNFPII in the first month of life may be protective against rapid infant weight gain in the first 6 months, regardless of HMO secretor status. These findings provide additional evidence that specific human milk components may diminish infant obesity risk. Funding Sources: Supported by the National Institute of Diabetes and Digestive and Kidney Diseases (NIH R01 DK110793) and the Gerber Foundation.